Effects of Intraoperative Fluid Management on Postoperative Outcomes After Pericardiectomy - Fang, Likui; Zheng, Hong; Yu, Wenfeng; Chen, Gang; Zhong, Fangming (Frontiers in Surgery, 2021)
Background The effects of intraoperative fluid management on the patients with constrictive pericarditis undergoing pericardiectomy remain unclear. This study explored the relationship between intraoperative fluid management and postoperative outcomes in these patients. Methods We retrospectively studied 92 patients with constrictive pericarditis undergoing pericardiectomy and assigned them to the restrictive group and the liberal group according to the intraoperative total fluid infusion rate. Postoperative outcomes were compared between the two groups. Binary logistic regression analysis was performed to determine the relationship between the intraoperative total fluid infusion rate and postoperative outcomes. Results There were 46 (50.0%) cases in the restrictive group and 46 (50.0%) cases in the liberal group. Compared with the liberal group, the restrictive group had significantly lower incidences of postoperative complications and cardiac complications (P=0.005 and P=0.006, respectively). Binary logistics regression analysis also showed the increased risks of postoperative complications (OR, 3.551; 95%CI, 1.192-10.580; P=0.023) and cardiac complications (OR, 6.037; 95%CI, 1.472-25.052; P=0.013) at the liberal group. In addition, the restrictive group had shorter postoperative hospital stay (P=0.026) in comparison to the liberal group. Conclusion In patients with constrictive pericarditis undergoing pericardiectomy the intraoperative total fluid infusion rate was significantly associated with postoperative outcomes. Restrictive fluid management strategy was related to the positive effects on enhanced recovery after surgery and could be advised as the preferred intraoperative fluid management policy.